The rise of the Taiwanese table tennis new star Lin Yun-Ju - Wu, T. Y.; Chin, H. P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
After capturing a bronze medal in the mixed doubles, at the Tokyo 2020 Summer Olympics, Lin Yun-ju vaults into stardom in the world of table tennis. This study employs case study research method to investigate the upbringing, performance and playing style of Taiwanese table tennis paddler Lin Yun-ju. Through investigation we found that: 1. Both of Lin`s parents work as educators. He started playing table tennis at the age of 10, and became the youngest representative in the national team at 2015 (14 years old). 2. In the 2019 T2 Diamond tournament, Lin defeated Jun Mizutani, Ma Long and Fan Zhendong consequently won the championship and make a name for himself. He then partnered with Cheng I-ching to win bronze medal at the Tokyo 2020 Summer Olympics, subsequently won the championship at WTT Champions Frankfurt 2023. His massive success shocked the world of table tennis. 3. Lin takes advantage on his left-handed dominance and coupled with balanced rhythm control as his major playing trait. He poses a more aggressive style in serving and attacking, his transition from the backhand flick after receiving serves to the seamless and accurate connection of forehand and backhand is highly smooth. To sum, Lin begins to learn the sport of table tennis at very young age, and different levels of trails and competitions brining him a solid foundation to stand out in the international stage, which able to showcase his talent in the sport. He rose from relative obscurity to worldwide recognition as a new star in the world of table tennis.